The Influence of Green Human Resource Management and Green Transformational Leadership in Shaping Green Employee Behavior in Private Elementary Schools - Rachmi Hadiyati, Noer; Anandita, Rina (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
Although Green Employee Behavior (GEB) has been extensively explored in corporate and business environments, far less attention has been given to its development within educational institutions, particularly private elementary schools. In fact, schools hold a vital role in nurturing sustainability values from an early stage through the example set by educators. This study investigates how Green Human Resource Management (GHRM) and Green Transformational Leadership (GTL) contribute to shaping Green Employee Behavior (GEB), while also examining the mediating roles of Green Knowledge Sharing (GKS) and Employee Environmental Awareness (EEA). Using a quantitative explanatory approach, data were gathered through a survey of 214 permanent teachers from private elementary schools across five areas of Jakarta. Responses were measured using a five-point Likert scale and analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that GHRM positively influences GEB both directly and indirectly through Green Knowledge Sharing. In addition, Green Transformational Leadership strengthens Green Employee Behavior by enhancing Employee Environmental Awareness and encouraging knowledge-sharing practices among educators. Practically, the study suggests that schools should implement structured green HR policies, promote collaborative green knowledge-sharing practices, and develop transformational leadership competencies to foster environmental awareness and sustainable employee behavior in educational institutions.